Dietary licorice flavonoids powder improves serum antioxidant capacity and immune organ inflammatory responses in weaned piglets - Yin, Shenggang; You, Ting; Tang, Jiayong; Wang, Longqiong; Jia, Gang; Liu, Guangmang; Tian, Gang; Chen, Xiaoling; Cai, Jingyi; Kang, Bo; Zhao, Hua (Frontiers in Veterinary Science, 2022)
Weaning often induces oxidative stress and inflammatory response in piglets. This study investigated the effects of dietary licorice flavonoids powder (LFP) supplementation on antioxidant capacity and immunity in weaned piglets. 96 Landrace × Yorkshire × Duroc (DLY) weaned piglets were randomly allocated to four treatments with 6 replicates (4 animals per replicate) and fed with diet supplementation with 0, 50, 150, and 250 mg/kg LFP respectively. The trial lasted for five weeks. The results showed that dietary LFP supplementation effectively increased the liver index (P < 0.05). In addition, dietary LFP supplementation reduced serum aspartate aminotransferase activity (P < 0.01). Piglets fed with 50 mg/kg LFP decreased total cholesterol and HDL-C content in serum (P < 0.05) and increased serum alkaline phosphatase activity (P < 0.01). Similarly, supplementation with 150 mg/kg LFP elevated the activity of total antioxidant capability (T-AOC) in serum (P < 0.01) and dietary with 150 and 250 mg/kg LFP increased T-AOC activity in spleen (P < 0.01). Moreover, dietary with 150 mg/kg LFP addition enhanced (P < 0.05) the serum IgG content of piglets. Additionally, Compared with the control group, dietary 250 mg/kg LFP supplementation up-regulated (P < 0.05) the mRNA abundance of Interleukin (IL)-1β and monocyte chemoattractant protein 1 (MCP-1) in spleen. Meanwhile, dietary 150 and 250 mg/kg LFP supplementation down-regulated (P < 0.05) mRNA abundance of IL-10, MCP-1 and 250 mg/kg LFP up-regulated (P < 0.05) the expression of intercellular adhesion molecule 1 (ICAM-1), IL-1β, IL-6, and tumor necrosis factor α (TNF-α) in thymus. In conclusion, LFP supplementation improved the immune function of piglets by regulating the activity of serum biochemical enzymes, improving the antioxidant capacity and alleviating inflammation of immune organs. This study indicated that LFP is potential alternative protection against early-weaned stress in piglets.